Recuperating Errors in Using Gerunds and Infinitives by Applying Duolingo Gamification - Aurorra, Gryzel; Usadiati, Wahyuningsih; Widiastuti, Oktavia (Fakultas Ilmu Budaya, Universitas Brawijaya, 2025)
The specific aim of this research is to recuperate Grammar Mastery (GM) in high school students who have difficulty distinguishing between gerunds and infinitives. Conventional learning methods often fail to teach effectively to students, necessitating the exploration of alternative learning approaches. This research examines the impact of Duolingo Gamification (DG) on students’ GM of gerunds and infinitives compared to conventional learning methods. A quasi-experimental research design was used, involving 42 students of Senior High School in Malang who were divided into an experimental group receiving the treatment using Duolingo and a control group having conventional learning based on textbook. Data were collected through pre-test and post-test to evaluate the enhancement of student’s grammar mastery. Statistical analysis including the Mann-Whitney U test revealed significant differences between the two groups of U = 40.500, p = 0.000. The experimental group obtained a higher mean post-test score (M = 81.66) than that of the control group (M = 45.71). The final results show that DG effectively recuperates GM of gerund and infinitives. Additionally, students show increased engagement and motivation when using Duolingo due to its interactive elements and direct feedback mechanisms.